2006
DOI: 10.6009/jjrt.62.734
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of LCD and CRT Monitors for Detection of Pulmonary Nodules and Interstitial Lung Diseases on Digital Chest Radiographs by Using Receiver Operating Characteristic Analysis

Abstract: Soft copy reading of digital images has been practiced commonly in the PACS environment. In this study, we compared liquid-crystal display (LCD) and cathode-ray tube (CRT) monitors for detection of pulmonary nodules and interstitial lung diseases on digital chest radiographs by using receiver operating characteristic (ROC) analysis. Digital chest images with a 1000x1000 matrix size and a 8 bit grayscale were displayed on LCD/CRT monitor with 2M pixels in each observer test. Eight and ten radiologists participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Furthermore, Uematsu and Kasami [21] showed that soft-copy reading of a digital mammography of mass with 3 megapixel LCD monitors was similar in diagnostic performance to 5 megapixel CRT monitors and 3 megapixel LCD monitors can replace 5 megapixel CRT monitors without any loss in the ability to diagnose digital mammograms. Some other reports are also congruent with the above results of our study [6,[17][18][19][20][21][22][23][24][25]. Therefore, we believe that the results are generally applicable.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, Uematsu and Kasami [21] showed that soft-copy reading of a digital mammography of mass with 3 megapixel LCD monitors was similar in diagnostic performance to 5 megapixel CRT monitors and 3 megapixel LCD monitors can replace 5 megapixel CRT monitors without any loss in the ability to diagnose digital mammograms. Some other reports are also congruent with the above results of our study [6,[17][18][19][20][21][22][23][24][25]. Therefore, we believe that the results are generally applicable.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, many studies have attempted to determine the applicability of new display devices in digital imagereading practice as compared with legacy display devices, such as screen-film systems vs CRT monitors, CRT monitors vs LCDs, and monochrome vs colour monitors [1,2,4,9,10,[17][18][19]. However, to date, no studies have reported any significant differences between the different types of display devices used in diagnostic imaging practices.…”
Section: Discussionmentioning
confidence: 99%
“…Ikeda et al [10] suggested that the detectability of pulmonary nodules and interstitial lung diseases in chest images displayed on a CRT and LCD was almost comparable. Krupinski et al [11] concluded that maximum-luminance LCDs with as high as 450 cd/m 2 may have an advantage in terms of diagnostic accuracy and visual search efficiency for detecting lung nodules in chest images, compared to lowermaximum-luminance monochrome and color LCDs, although these differences may have little clinical impact because they are relatively small.…”
Section: Introductionmentioning
confidence: 98%
“…4,[8][9][10][11] More recently, Ikeda et al reported that there was no signifi cant difference between LCD and CRT monitors with 2M pixels for both detection performance of pulmonary nodules and interstitial lung diseases on digitized chest radiographs. 19 Furthermore, Araki et al showed that no signifi cant differences in the nodule detection performance on chest radiographs were detected among the monochrome LCD monitors with 3M and 5M pixels and the color LCD monitors with 3M pixels. 20 Their reports are also congruent with the above results of our present study.…”
Section: Discussionmentioning
confidence: 98%